Retrofitting the built environment - Swan, William, 1972-; Brown, Philip, 1977-; ProQuest (Firm) (Chichester, West Sussex : Wiley-Blackwell, 2013)
"Retrofitting the Built Environment is an extension of this conference. Contained within is a mix of policy, technical and social science papers, presented by both academic and industry authors, giving a multiple perspective of the issue from both a UK and international perspective"--
pt. 1. Understanding the problem -- pt. 2. Policy and regulation -- pt. 3. Implementing and evaluating retrofit -- pt. 4. Peoples and communities.
Includes bibliographical references and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Housing policy -- Great Britain; Architectural design -- Great Britain; Housing policy; Social history; Architectural design; Great Britain -- Social conditions; Electronic books